Microglial M2 Polarization Mediated the Neuroprotective Effect of Morroniside in Transient MCAO-Induced Mice - Hao Liu; Mei-Xian Ou; Qiao-Qiao Han (Frontiers Media S.A., 2021)
Morroniside, a secoiridoid glycoside from Cornus officinalis, is a class of small molecule non-peptide glucagon-like peptide-1 receptor (GLP-1R) agonists and possess many important biomedical functions. Our previous studies reported that GLP-1R agonist exenatide promoted M2 polarization and the expression of cell-specific anti-inflammatory factor interleukin-10 in neuropathological pain model. In this study, we proved that morroniside not only induced M2 polarization and stimulated interleukin-10 expression specifically in cortical primary microglia by p38β mitogen-activated protein kinases pathway but also protected nerve cells against H2O2-induced cell oxidative damage and prohibited ischemic injury by reducing infarct size, which is at least in part mediated by enhanced expression of microglial interleukin-10. In the cortical penumbra area in middle cerebral artery occlusion (MCAO) mice. In general, our results indicated that GLP-1R agonist morroniside might play a neuroprotective effect by inducing M2 polarization, and cyclic-AMP/protein kinase A/p38β pathway might mediate morroniside-induced expression of interleukin-10 protein in M2 microglia.